Engineering Building with a car and water tower, University of Washington, Seattle, ca. 1915 - University of Washington Libraries. Special Collections Division (1915)
Formerly Machinery Hall during Alaska Yukon Pacific Exposition. PH Coll 655.29 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number